Electronic-Based Marketing Strategies in Building Competitive Advantages in Silk Weaving Small Businesses in Wajo District - Ilma Wulansari Hasdiansa; Sitti Hasbiah (Indonesian Journal of Business and Entrepreneurship Research, 2023)
This study aims to determine the internal and external constraints on silk artisans. This research uses a qualitative descriptive method. The data used in this study are primary and secondary data, this data was obtained by researchers through observation, interviews, and documentation. The results of this study indicate that the electronic-based marketing strategy in building competitive advantages in small silk artisan businesses in Wajo Regency is by conducting a product marketing mix, determining the selling price of products based on the price of Production Operating Costs, a strategic and easily accessible business place, and promotions carried out, namely offline and online promotions. While the obstacles experienced by silk entrepreneurs in carrying out marketing strategies through Facebook social media are internal and external obstacles. The solution to overcome internal obstacles is to carry out an order system, self-taught learning through youtube media. for external obstacles is to provide affordable prices by using quality materials, be more creative and provide the best service, provide rich writing bounty marks on every picture posted, provide clear information, especially the prices offered.